Dinamika Pendidikan Madrasah Ibtidaiyah di Lampung Timur: Analisis terhadap Peran Guru dalam Menghadapi Era Pendidikan Inklusif - Anita Puspa Meilina (IHSANIKA : Jurnal Pendidikan Agama Islam, 2025)
This study aims to examine the dynamics of education in Madrasah Ibtidaiyah (Islamic elementary schools) in East Lampung in addressing the challenges of inclusive education, with a focus on the role of teachers in implementing teaching practices that accommodate students with special needs. The research employs a qualitative approach using semi-structured interviews, classroom observations, and document analysis as data collection instruments. The findings reveal that teachers in MI East Lampung face several obstacles, including insufficient training and limited facilities to support inclusive education. Nevertheless, teachers strive to adapt their teaching methods to accommodate students with special needs, supported by government policies and collaboration with parents. This study recommends enhancing teacher training, providing adequate facilities, and strengthening partnerships between schools and parents to foster a more inclusive educational environment. Furthermore, the research encourages future studies on the use of technology to support inclusive education in Madrasah Ibtidaiyah.